Sulphur status in Finnish cultivated soils - Johan Korkman (Scientific Agricultural Society of Finland, 1973)
A method for determining total sulphur in plant material and soil samples using the induction furnace technique and subsequent turbidimetric determination of sulphate sulphur was discussed. A procedure for extracting sulphur from soil samples with ammonium acetate (pH 4.65), the interference of the organic matter being reduced by oxidation of the extract with H2O2, was proposed. Sulphur balance in Finnish cultivated soils was estimated by taking into account the average amounts of emitted (8 kg S/ha/yr.), precipitated (8 kg S/ha/yr.) and leached (8 kg S/ha/yr.) sulphur. The actual situation in the cultivated soils seems thus to be depending, on an average, on the uptake by plants and the sulphur applied (12 kg S/ha/yr. in the early 1970s). In 104 samples of cultivated soil, the content of total sulphur showed a slight correlation with the content of organic carbon. The amounts of sulphur extracted in various ways were not predictable by means of the soil characteristics used (pHCaCl2, org. C and texture). Extracted sulphur did not correlate sufficiently with the development and sulphur uptake of plants. Under field conditions in northern Finland, sulphur application produced a relatively distinct result in respect both to the ley yields on Carex peat, and their sulphur content. On mineral soils in southern Finland the yields were unaffected by supplementary fertilization with sulphur. In the pot experiments performed a fairly close relationship between sulphur and nitrogen was demonstrated.